Assessment of Clinical Conditions Associated With Splenic Infarction in Adult Patients - Brett, Allan S. (JAMA Intern Med, 2020)
This case series examines the clinical conditions associated with splenic infarction of adult patients between 2010 and 2015 from computed tomographic imaging scans.